LPG Representation of the Reification of RDF - Zaho, Zhanfang; Kook Han, Sung; Ri Kim, Ju (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is still a challenging issue to represent the reification effectively since the reification representation of RDF standard has been revealed some drawbacks.Methods/Statistical analysis: Currently, there are two main graph data models: RDF and LPG. LPG is a popular graph data model that is usually applied to NoSQL graph databases.This paper derives three types of the reification structures in terms of the structural and semantic relationships of the reification statements. The detailed representation of each type of the reification is presented with the extended LPG model.Findings: This paper proposes a novel approach to represent the reification structure of RDF from the perspective of LPG. The paper explores the formal, conceptual properties of the conventional LPG models and proposes their extension to capture more complex knowledge structures efficiently. These augmentations of LPG can achieve more efficient and flexible resource modeling. This paper derives three types of the reification structures in terms of the structural and semantic relationships of the reification statements: assertion, quantification, and entailment.The proposed approach not only preserves the structure and semantics of the reification but also enables LPG modeling of the complex structural statements to be easy and intuitive.This can contribute to transfer RDF graphs into LPGs.Improvements/Applications: The implementation of the extended LPG and the query processing of the reification remain future work.Â